Top-level design of intelligent city constructed on provincial CATV networks - Yi CHEN; Baocheng LIN; Xianhu WEI; Longxiang YANG; Fengqiang PENG (Dianxin kexue)
The top-level design of the intelligent city constructed on provincial CATV networks was mainly investigated. The general thoughts of the development of intelligent city constructed on CATV networks were proposed, and the overall framework for the intelligent city constructed on CATV networks was analyzed.